Дослідження парамагнітних координаційних сполук лантаноїдів складу [LnL3 • Phen] (L = CCl3C(O)NP(O)(OCH3)2) методом ЯМР-спектроскопії на ядрах 1H та 31P - Trush, V. A.; Litsis, O. O.; Sliva, T. Yu.; Gumenyuk, Ya. O.; Amirkhanov, V. M. (Publishing house "Academperiodika", 2019)
A series of lanthanide coordination compounds with dimethyl-N-trichloroacetylamidophosphate CCl3C(O)N(H)P(O)(OCH3)2 (HL) [HL = CCl3C(O)N(H)P(O)(OCH3)2 is a ligand of the carbacylamidophosphate (CAPh) type], whose compositions are described by the formula [LnL3 · Phen], where Ln = La, Ce, Pr, Nd, Sm, Tb, Dy, Ho, and Er; L is the deprotonized form of HL; and Phen is 1,10-Phenantroline, has been synthesized. Acetonic solutions of HL and complexes synthesized on its basis are studied by means of 1H- and 31P-NMR spectroscopy at room temperature (298 K). Since the chemical shifts of 1H signals have the pseudocontactorigin, the isotropic shifts of 31P signals are managed to be decomposed into the contact and pseudocontact components. It is found that there are two series of complexes in the solution of [LnL3 · Phen] compounds with the same structure of the coordination sphere within each of the series Ln = (Ce, Pr, Nd, Sm) (series L1) and Ln = (Tb, Dy, Ho, Er) (series L2). The values of the constant of superfine interaction for those complexes are calculated: 0.18 MHz (series L1) and 0.13 MHz (series L2).